A Comparison between Different Types and Frequency of Physiotherapy Treatment for Children and Adolescents with Postural Problems and Low Back Pain. (4th March 2022) - Vitman, Neta; Hellerstein, Devora; Zeev, Aviva; Gilo, Yael; Nakdimon, Oren; Peretz, Asaf; Eilat-Adar, Sigal
Abstract: Aim: To examine the effect of a once-a-week group physiotherapy session in addition to a once-a-month individual physiotherapy treatment, in comparison to a monthly individual physiotherapy treatment. Methods: Fifty children and adolescents aged 10-18 years with poor back posture, some of whom had LBP, met individually with a physiotherapist once a month. The intervention group received an additional once-a-week group physiotherapy session for 12 weeks. Thorax curve angle, postural behavior, and low back pain (LBP) were measured before and after intervention. Results: The thorax curve angle decreased from 39.2 ± 9.3 to 28.2 ± 6.8 (p < 0.001) in the group + individual therapy group and from 38.9 ± 9.3 to 27.9 ± 7.8 in the individual therapy only group (p < 0.001). LBP decreased from 5.6 ± 2.2 to 1.6 ± 1.9 (p < 0.001) and from 5.5 ± 2.1 to 2.8 ± 2.0 (p < 0.001). A significantly greater improvement in postural behavior was found in the group + individual therapy group (p = 0.04). Moreover, attrition rates were lower in the experimental group. Conclusion: A lower-frequency individual physiotherapy treatment for 12 weeks proved as beneficial as the same program with an additional higher-frequency group physiotherapy in improving thorax curve angle and LBP. However, the higher-frequency group physiotherapy in addition to the lower-frequency individual treatment was significantly more effective in improving postural behavior and adherence to treatment.